Construction and operation of a dispersive laser raman spectrograph using interference filter - Abedin, KM; Farhad, SFU; Islam, MR; Talukder, Aminul I; Haider, A F M Yusuf (© 2008 Journal of Bangladesh Academy of Sciences, 2017)
This article was published in the Journal of Bangladesh Academy of Sciences [© 2008 Journal of Bangladesh Academy of Sciences] and the definite version is available at: http://dx.doi.org/10.3329/jbas.v32i1.2451